Investigation on the genetic variability of the american pit bull terrier dogs belonging to an italian breeder using microsatellite markers and genealogical data - Ciampolini, R.; Cecchi, F.; Paci, G.; Policardo, C.; Spaterna, A. (Цитология и генетика, 2013)
The genetic variability of 18 American Pit Bull Terriers bred in Italy was studied using 21 STR markers from the panels recommended for the 2006, 2008 and 2010 ISAG canine comparison test and the genealogical information. As expected, all statistical analysis showed a reduced genetic variability. It is there-fore recommended greater attention in the programming of mating with an increase of gene flow among farmers, which would reduce the average inbreeding in the population and increase genetic variability.